2017
DOI: 10.1590/1980-4415v31n58a16
|View full text |Cite
|
Sign up to set email alerts
|

Dificultades Metodológicas en la Investigación sobre Pensamiento Matemático Indígena y su Paradójica Educación Matemática

Abstract:  ResumenEl objetivo de esta investigación consistió en determinar cuáles son las principales dificultades que afronta el investigador en etnomatemática cuando indaga sobre el pensamiento matemático indígena y es ajeno a esta comunidad. La metodología empleada para establecer esto, fue hacer un análisis de investigación documental, tomando como referencia gran parte de los textos producidos en Colombia. Este análisis permitió que emergieran categorías que se clasificaron como dificultades. Se concluyó que est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…The Aymara converse with nature, for them all have life and live in harmony with their environment (trees, animals, hills, among others) [10], it is also observed that the inhabitants of the communities define their lands, belongings, changes social, adaptations; information that are essential to understand and characterize different cultures [11] and in this way they can be rescued.…”
Section: Introductionmentioning
confidence: 99%
“…The Aymara converse with nature, for them all have life and live in harmony with their environment (trees, animals, hills, among others) [10], it is also observed that the inhabitants of the communities define their lands, belongings, changes social, adaptations; information that are essential to understand and characterize different cultures [11] and in this way they can be rescued.…”
Section: Introductionmentioning
confidence: 99%